Effects of information overload on news consumer behavior: The doomscrolling - Camacho Fernández, Patricia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The increasing amount of information available on digital media platforms forces some media consumers to simply skim content without having time to verify its accuracy and authenticity (Aspach, 2017). This simplification of news processing might also diminish the ability of their consumers to identify fake news and simply trust the selective media sources they perceive as credible. In this article, we aim to analyse the link between the aforementioned information overload and the perception of fake news and the selective and compulsive consumption of negative news.